Introdução ao estudo de funções geradoras - Rodrigues, Júlio César Prado Souza (2018)
In this work, our goal is to present some combinatorial problems that can be solved using the Generating Functions and also to show that this study can contribute to future research as well as to new methodological possibilities for the teaching of Mathematics.